MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK DENGAN MODEL PEMBELAJARAN SAVI BERBANTUAN MEDIA WORDWALL DALAM PELAJARAN IPAS KELAS IV MIN 7 BANDAR LAMPUNG (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Study This aim analyze How application of the SAVI learning model in increase activity Study participant students in science learning with with the help of wordwall media at MIN 7 Bandar Lampung. Subject study is student Class IV of MIN 7 Bandar Lampung. The method used was Classroom Action Research (CAR) with approach qualitative and quantitative. The instruments used in study covering sheet questionnaire, observation and documentation. Research considered succeed if at least 75% of students has reach level activity Study with category active. Research This implemented in two cycles, each cycle consists of from two meetings with stages planning, implementation, observation, and reflection. Research results show that in cycle I the activity Study participant educate reached 69,6% while in cycle II it increased to 77,6%. Achievement This has exceed criteria success that has been determined. With Thus, the application of the SAVI learning model assisted by word wall media proven effective in increase activity Study participant educate class IV at MIN 7 Bandar Lampung.